What is the solution to the following system of equations? 2x + 3y = 6 x + y = 4 The solution of the system of equations is

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

What is the solution to the following system of equations? 2x + 3y = 6 x + y = 4 The solution of the system of equations is

Algebra
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

step # 1 call the equations as 2x+3y =6.............. eq # 1 x+y=4.............eq #2 step #2 isolate the x from the most simplest equation I took equation 2 x = 4-y ....... eq#3 I called this equation as equation 3 Step # 3 now put the x =4-y into the equation 1 at the place of x so equation 1 becomes 2 (4-y) +3y = 6 8-2y + 3y = 6 8 + y =6 y=6-8 y=-2 now u will put y=-2 into equation 3 at the place of y since x = 4-y x = 4 - (-2) x = 4+2 x= 6 so x= 6 and y =-2 this is your solution
@mrkdc2 if you have any question regarding this explanation ask me.
no i dont thank you

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Welcome

Not the answer you are looking for?

Search for more explanations.

Ask your own question